2020
DOI: 10.3390/su12208378
|View full text |Cite
|
Sign up to set email alerts
|

Employee Volunteerism—Conceptual Study and the Current Situation

Abstract: The purpose of the study is to analyze employee volunteerism. This issue had not been studied on a broader international level earlier. This research firstly discovers altruism and volunteerism values in the economy. Then, based on the third-party model, observes each part, where participants are the (1) volunteer (employee) (2) company (and its CSR activity) and (3) an external organization, which manages this type of formal volunteerism. Each participant was analyzed through comprehensive analysis using desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Notably, Ramelli and Wagner 27 and Albuquerque et al 31 observed varying stock price trends throughout the pandemic. Economic repercussions of COVID-19 extend to significant social implications, such as job disruptions, widespread unemployment, and reduced work hours in the labor market 32 .…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Notably, Ramelli and Wagner 27 and Albuquerque et al 31 observed varying stock price trends throughout the pandemic. Economic repercussions of COVID-19 extend to significant social implications, such as job disruptions, widespread unemployment, and reduced work hours in the labor market 32 .…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…CV raises concerns regarding the responsibilities and rights of the volunteers once the volunteering law and framework can be complex and not clear. Experts affirm that companies should acquire liability insurance to prevent those risks, recommending companies to develop guidelines with specific roles description and clearly organize recruitment, training, orientation, management and program evaluation (Bauer, 2017;Loosemore & Bridgeman, 2018, Derecskei & Nagy, 2020.…”
Section: Impacts In the Companymentioning
confidence: 99%
“…22 Companies that have used CSR even before crises will experience fewer losses, be more resilient, and take a shorter time to recover from attacks, unlike those companies that did not have or had weak CSR activities. 23 Likewise, consumer sensitivity is greatest in times of crisis, and their perception of a company that carried out CSR activities during the crisis will positively affect their product consumption, punishing those who do not react in this way. 24 on CSR for marketing purposes, the initial positive customer perception of that company changes.…”
Section: The Importance Of Csr In Times Of Crisismentioning
confidence: 99%